#TITLE_ALTERNATIVE# - BUNDONG SIHITE (NIM : 13705041); Pembimbing : Dr. Ir. Husaini Ardy , PAOLO
Annealing is a heat treatment process to change the grain size and hardness of metals. This process often used before and after forming process. The forming process of metals into another products can be done by hot or cold working. The main purpose of annealing process of metals that have underwent forming process is to achieve the optimum mechanical properties which affected by two primary factors, time and temperature of annealing. This research is conducted to study the effect of annealing time on the hardness of metals after the cold working process. Parameters of this research are annealing time, εt, and grain size. Specimen used in this research is four pieces of Cu-Sn-Pb alloy with the same dimensions. All of the specimen was annealled and rolled. Annealing process has been done in two steps with different heating time; annealing I (before rolling) and annealing II (after rolling). The rolling process was conducted up to 80% of plastic deformation. The characterization methods for each specimen are hardness test and metallography. Those methods employed to determine the effect of grain size to the hardness of metals. Grain size measurement was conducted by linear intercept method. The maximum hardness value obtained in this research is 115 VHN with plastic deformation of 80%, and annealing II of 15 minutes at 650oC. The hardness values according to standard specification (ASTM B 103) for bearing application is 121 VHN, therefore, this specimen has not met standard specification. Additional treatment has been done to achieve the standard specification hardness. This methods has been carried out by performed annealing II for 11 minutes which result in the hardness of 121 VHN. Grain size of Cu-Sn-Pb alloy increased from 55 Mm to 77m after annealing II. This data gave evidence that with longer annealing time, the grain size would increase and the hardness value of Cu-Sn-Pb alloy would decrease.